Tentoonstelling Nul. (Amsterdam : Stedelijk Museum Amsterdam, 1962)
Arman ; Armando ; Aubertin, Bernard ; Bury, Pol ; Castellani, Enrico ; Dorazio, Piero ; Fontana, Lucio ; Goepfert, Hermann ; Haacke, Hans ; Henderikse, Jan ; Holweck, Oskar ; Kusama Yayoi ; Mack, Heinz ; Maino, Dada ; Manzoni, Piero ; Mavignier, Almir ; Megert, Christian ; Peeters, Henk ; Piene, Otto ; Pohl, Uli ; Savio, Francesco Lo ; Schoonhoven, Jan ; Uecker, Günther ; Verheyen, Jef ; de Vries, Herman
Tentoonstelling Nul, Stedelijk Museum Amsterdam, 9-25 maart 1962
Nederlands
boek